2020
DOI: 10.3390/cancers12051083
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Prostate Cancer Cells and Tumor-Associated Fibroblasts Enhances the Malignancy by Inhibiting the Tumor Suppressor PLZF

Abstract: Although prostate cancer is clinically manageable during the early stages of progression, metastatic progression severely compromises the prognosis and leads to mortality. Constitutive activation of STAT3 has been connected to prostate cancer malignancy, and abolishing the STAT3 activity may diminish tumor growth and metastasis. However, its suppressor genes and pathways have not been well established. In this study, we show that promyelocytic leukemia zinc finger (PLZF) has a putative tumor-suppressor functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The level of STAT3 was increased in high-grade NMIBC tumors. It was also found useful to distinguish cancer type [38,40]. Elevated pSTAT3 Ser727 level was associated with significantly poorer prognosis, higher cancer recurrence rate and lower cancer-specific survival in UTUC.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 96%
See 1 more Smart Citation
“…The level of STAT3 was increased in high-grade NMIBC tumors. It was also found useful to distinguish cancer type [38,40]. Elevated pSTAT3 Ser727 level was associated with significantly poorer prognosis, higher cancer recurrence rate and lower cancer-specific survival in UTUC.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 96%
“…On the other hand, fibroblasts produce CCL3, which prevents PLZF expression. Scientists presented a part of complicated relationship between fibroblasts and PCa cells, describing a potentially useful CCL3/PLZF/SHP1/STAT3 cascade [40]. Zhao et al reported that highly concentrated lactoferrin (LTF) significantly decreases STAT3 and granulocyte-macrophage colony-stimulating factor (GM-CSF) levels, which result in immune TME changes [41].…”
Section: Role Of Stat3 In Prostate Cancermentioning
confidence: 99%